Study of Human Rights in the State of The Rule of Law: Between Progressive Law and Positive Law - Mukhamad Luthfan Setiaji; Aminullah Ibrahim (Lex Scientia Law Review, 2018)
The formation of the law cannot be separated from the judges of judges (judge made law) related to law enforcement, while law enforcement is essentially a process to realize the legal objectives of legal ideas into reality. This paper examines aspects of human rights in the rule of law, between progressive law and positive law. Progressive law is a pro -justice and pro -people law, meaning that the law of legal actors is required to prioritize honesty, empathy, concern for the people and sincerity in law enforcement.